Transforming engineering education in the digital era: findings from a systematic review - Hsu, Yu-Ping; Chiang, Danielle F.; Kehinde, Ifedayo (Frontiers in Education, 2025)
IntroductionAccording to the Digital Curricula Report on the status of online learning in higher education in the United States, about one-third of higher education is online, a number that has substantially increased after the pandemic (Analytics, 2022). As of October 1, 2024, the Accreditation Board for Engineering and Technology (ABET) has accredited 3,611 programs across 702 institutions in the United States, but only 46 institutions offered 100% online programs, which is significantly lower than other fields. This study aims to explore the factors that influence the acceptance of online learning and teaching in engineering education from the perspectives of students and teachers after the COVID-19 pandemic.MethodsThis study followed the PRISMA guidelines and included only peer-reviewed articles published between 2020 and 2024, focusing on online engineering education. This systematic review explored the variables affecting student and teacher acceptance of online learning in order to more clearly define challenges in delivering online engineering education and to identify avenues to improve and strengthen it. The inclusion criteria focused on articles addressing instructional design and learning experiences in online education, while the exclusion criteria eliminated studies without key data and those outside the specified timeframe.DiscussionThe findings of this systematic review highlighted several factors influencing the acceptance of online engineering education, such as technology design, individual characteristics, and social factors. These factors are important for creating effective, engaging, and accessible learning environments that enhance student performance and satisfaction. Further research is needed to develop an approach to examine factor interactions in different contexts, and create a framework aligned with ABET accreditation standards for assessing long-term learning outcomes.